BrachyView: Reconstruction of seed positions and volume of an LDR prostate brachytherapy patient plan using a baseline subtraction algorithm. (October 2019) - Brennen, T.; Cutajar, D.L.; Alnaghy, S.; Bucci, J.; Bece, A.; Enari, K.; Favoino, M.; Carriero, F.; Tartaglia, M.; Galli, L.; Lerch, M.; Rosenfeld, A.B.; et al.
Highlights: The BrachyView system displays a detection rate of 100 Seed positions for CT and the BrachyView system were fused with the 3D volume, reconstructed from TRUS images. An 11.5% reduction in positon accuracy was noted without baseline subtraction application. Without baseline subtraction a 7.6% and 2.1% reduction in the D90 and V100, respectively, were noted. Abstract: Purpose: BrachyView is a novel in-body imaging system developed with the objective to provide real-time intraoperative dosimetry for low dose rate (LDR) prostate brachytherapy treatments. The BrachyView coordinates combined with conventional transrectal ultrasound (TRUS) imaging, provides the possibility to localise the effective position of the implanted seeds inside the prostate volume, providing a unique tool for intra-operative verification of the quality of the implantation. This research presents the first complete LDR brachytherapy plan reconstructed by the BrachyView system and is used to evaluate the effectiveness of an imaging algorithm with baseline subtraction. Methods: A plan featuring 98 I-125 brachytherapy seeds, with an average activity of 0.248 mCi, were implanted into a prostate gel phantom under TRUS guidance. Images of implanted seeds were obtained by the BrachyView after the implantation of seeds. The baseline subtraction algorithm is applied as a pixel-to-pixel counts subtraction and is applied to every second projection obtained after the implantation of each needle. Seed positions and effectiveness of the baseline reconstruction in the identification of seeds were verified by a high-resolution post-implant CT scan. Results: A complete brachytherapy plan has been reconstructed with a 100% detection rate. This is possible due to the effectiveness of the baseline subtraction, with its application an overall increase of 11.3% in position accuracy and 8.2% increase in detection rate was noted. Conclusion: It has been demonstrated that the BrachyView system shows the potential to be a solution to providing clinics with the means for intraoperative dosimetry for LDR prostate brachytherapy treatments.